Prosthetic Arm for Amputees: Labor Job in Manufacturing Factories - Aguda, Robyn Graesha O. (Animo Repository, 2021)
Unemployment occurs when an individual with a specified age range does not engage in work and is unpaid; furthermore, they are still looking for new job opportunities. Each person should be allowed to work and earn for their betterment, most significantly, people with physical disabilities. Most amputees utilize prostheses to resume daily tasks and adapt to a sudden lifestyle change to achieve this. This study aims to conceptualize and create a bodypowered transradial prosthesis designed to execute both functions of picking and placing actions, particularly for inspection in manufacturing labor, to aid the pressure of restoring a once normal lifestyle. Upon testing the said prosthesis, it had a weight capacity of at least 20 grams with a mechanical gripper’s aid to avoid slippage of the bottle. The general testing methods included 90 attempts in proving the prosthesis’ functionality and weighing capacity. To conclude, it had 87% and 80% successes in terms of the primary function in both stationary and mobile trials, respectively; further, the prosthesis succeeded in carrying bottles of varying weight with an overall rate of 87%